Storyworlds: dipper to the rescue - Hughes, Monica; McPhillips, Robert (Heinemann Educational UK, 1996)
When a storm hit the forest, Dipper, a young, fearless squirrel, raced through the trees to warn his friends. With swift leaps and clever tricks, he guided them to safety just as the winds howled. His bravery became the tale that echoed through the forest for generations.